Tanggapan Warga Belajar terhadap Komunikasi Instruksional Instruktur Pelatihan Memasak Kue di SPNF SKB Kota Payakumbuh - Maulidia Wahyumi; Wirdatul Aini; Irmawita Irmawita (Universitas Negeri Padang, 2018)
This research is motivated by the success of entrepreneurship cooking skill. The purpose of this study was to describe the responses of learners to instructional communication of cooking instructor in cooking instruction in the explanation of learning materials, initial ability assessment, strategy setting, and feedback. This type of research is descriptive quantitative. The population in the study amounted to 15 people. The sample in this study is the total number of respondents. Data collection techniques used were interviews, while data collection tools used interview guidelines. Data analysis techniques using the formula percentage. The result of the research showed that the respondent's response to instructional instruction of instructor in (1) explanation of learning material of cooking cake training is categorized very good, (2) assessment of early ability of learners of cake cooking training categorized very good, (3) instructional strategy stipulation cake cooking training categorized very good, (4) feedback cooking cake is categorized very well.